The risk of water, sanitation and hygiene on diarrhea-related infant mortality in eastern Ethiopia: a population-based nested case-control - Samuel Mebrahtom; Alemayehu Worku; Daniel J. Gage (BMC, 2022)
Abstract Background Diarrhea is still appeared to be as one of the leading global killers and disability-adjusted life-years lost, particularly in the infant and children. As per WHO, about 88% of diarrhea-related deaths are attributable to unsafe water, inadequate sanitation and insufficient hygiene, mainly in developing world. Thus, the main objective of this study was to find out the risk of such factors that contribute for diarrhea-related infant mortality in Eastern Ethiopia. Methods This study employed community based unmatched nested case-control study design in Eastern Ethiopia. The cases were infants who died from diarrheal disease while controls were those who survived their first year of life from September, 2016 to August, 2018. A total of 305 study subjects (61 cases and 244 controls) were included in the study. Infants dying from diarrhea were compared to four neighborhood controls in terms of several risk components of Water, Sanitation and Hygiene. Data were collected from mothers/care takers of infants using pre-tested structured questionnaires, and entered onto CSpro version 5.1 and transform to SPSS version 23 to analyzed potential risk factors. Findings Finding of this study revealed that the risk factors that found to be significantly associated with infant death from diarrhoea after adjustment for confounding variables included the age of mother with < 20 years old (P = 0.009, AOR: 0.01, 95% CI: 0.01, 0.47), unsafe drinking water storage (P = 0.013, AOR: 0.4, 95% CI: 0.18, 0.81), infants in households without point-of-use water treatment practices (P = 0.004, AOR: 0.21, 95% CI: 0.08, 0.61), households with unimproved sanitation (P = 0.050, AOR: 0.36, 95% CI: 0.13, 1.00), unsafe disposing of child feces (P = 0.014, AOR: 0.34, 95% CI: 0.15, 0.81), and improper management of solid waste (P = 0.003, AOR: 0.29, 95% CI: 0.13, 0.66). These exposure factors had lower risk for the contribution of infants dying from diarrhoea than those with their reference group in the study area. However, infants in households with improper management of liquid waste management showed strongly significant association which had three times more likely to occur diarrhea-related infant death (P = 0.010, AOR: 3.43, 95% CI: 1.34, 8.76). Similarly, infants whose mother/caretaker practiced hand washing with less critical time (one-two occasions) had three times greater risk to infant death from diarrhea than those who had practice more than three critical times of hand washing (P = 0.027, AOR: 3.04, 95% CI: 1.13, 8.17). Conclusion This study suggests that infants in households with improper management of liquid waste and hand washing practices with fewer occasions (one-two critical time) are a greater risk of getting a diarrhea-related infant death. Therefore, efforts should be made to ensure intervention taking such risk factors into consideration, typically in the infantile period.